Rhynchocephalians: The least known South American Lepidosaurs - Apesteguía, Sebastián (2016)
The history of Rhynchocephalia in South America is rich and complex. Although the Triassic forms were related to the global lineages, including clevosaurs and derived herbivorous forms, along Jurassic new lineages succeeded. These forms are closely related to other endemic Gondwanan species, all positioned southwards from the Central Gondwanan Desert. During the Cretaceous the presence of terrestrial and littoral rhynchocephalians, provided of a very derived dentition and large size, and belonging to at least three different lineages, shows that the clade diversity was still healthy. After K/Pg boundary at least two lineages survived in South America probably until the global cooling event at the Eocene–Oligocene boundary.